2005
DOI: 10.1007/s00787-005-0494-3
|View full text |Cite
|
Sign up to set email alerts
|

Childhood onset neuropsychiatric disorders in adult eating disorder patients

Abstract: These preliminary data suggest that COND may be common in patients with severe ED and should be kept in mind when treating these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
104
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 33 publications
9
104
0
6
Order By: Relevance
“…The results also suggest that ADHD youth with comorbid behavioral health disorders or who experience punitive parenting are at higher risk. These findings are in keeping with a growing literature that has documented an association between ADHD and ED among adults, [25][26][27][28][29] and may not be surprising given that youth with ADHD are at increased risk for a host of behavioral health and substance abuse disorders. Two prior literature reviews on ADHD and ED by Cortese [30] and Nazar [31] published in 2007 and 2008 respectively, provided overviews of studies in both children and adults.…”
Section: Discussionsupporting
confidence: 86%
“…The results also suggest that ADHD youth with comorbid behavioral health disorders or who experience punitive parenting are at higher risk. These findings are in keeping with a growing literature that has documented an association between ADHD and ED among adults, [25][26][27][28][29] and may not be surprising given that youth with ADHD are at increased risk for a host of behavioral health and substance abuse disorders. Two prior literature reviews on ADHD and ED by Cortese [30] and Nazar [31] published in 2007 and 2008 respectively, provided overviews of studies in both children and adults.…”
Section: Discussionsupporting
confidence: 86%
“…There is some evidence that eating disorders (ED) and ADHD may share common clinical features and that ADHD rates may be increased in ED. [1][2][3][4][5] One pilot study suggested rates of ADHD as high as 17% among a group of 30 female eating disorder patients. 5 Other studies have failed to find increased rates of ADHD in ED.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4][5] One pilot study suggested rates of ADHD as high as 17% among a group of 30 female eating disorder patients. 5 Other studies have failed to find increased rates of ADHD in ED. A large study of over 2,000 patients treated as inpatients for ED found rates of ADHD at 3% in those with anorexia nervosa and 9% in those with bulimia nervosa.…”
Section: Introductionmentioning
confidence: 98%
“…Rates of ASD may be higher among patients with eating disorders than in the general population (Treasure 2010), with ASD affecting nearly 20% of adults with anorexia nervosa (Wentz 2005). Adolescent girls with Asperger syndrome have more eating problems than their typically developing peers (Kalyva 2009).…”
Section: Eating Disordersmentioning
confidence: 99%
“…Adolescent girls with Asperger syndrome have more eating problems than their typically developing peers (Kalyva 2009). In those with severe and enduring eating disorders an unrecognised ASD may impede and complicate treatment, and worsen prognosis (Wentz 2005). Identification of ASDs in people with eating disorders is important, as treatment modalities may differ depending on whether an ASD is or is not present -for example, psychodynamic treatments are unlikely to be appropriate for patients with ASD.…”
Section: Eating Disordersmentioning
confidence: 99%